Subclinical myocardial dysfunction identified with speckle tracking echocardiography in young adults patients recovered from asymptomatic or mildly symptomatic SARS-CoV-2 infection. (4th February 2022) - Barosi, A; Bergamaschi, L; Cusmano, I; Colombo, C; Gherbesi, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Myocardial strain assessed with speckle tracking echocardiography is a sensitive marker of cardiac dysfunction, with long-term prognostic value in many cardiac conditions. Both left ventricular global longitudinal strain (LV-GLS) and right ventricular longitudinal strain (RV-LS) were affected by severe SARS-CoV 2 infection but little is known about cardiac involvement in patients with asymptomatic/mild disease that did not require hospitalization.  Aim: To assess if subclinical myocardial dysfunction could be identified using LV-GLS and RV-LS in patients with previous asymptomatic/mild SARS-CoV 2 infection. Methods: 40 young adults patients (70% males, mean age 24.4 ± 8.4 years), who had a confirmed diagnosis of SARS-CoV-2 infection and were asymptomatic or only mildly symptomatic, without previous known comorbidities/cardiovascular risk factors, were retrospectively included. Patients underwent standard transthoracic echocardiogram and speckle tracking echocardiographic study at least 3 months after diagnosis. A total of 44 age, sex, and body surface area comparable healthy subjects were used as control group.  Results: LV-GLS was within normal limits but significantly lower in the cases group compared to controls (-22.7 ± 1.6% vs. -25.7 ± 2.3%; p < 0.001). Left ventricular ejection fraction (63.3 ± 4.1% vs 63.9 ± 4.6%; p = 0.5), tricuspid annular plane systolic excursion (24.3 ± 3.7 vs. 23.7 ± 3.3; p = 0.5) and RV-LS (-23.2 ± 3 vs. -23.6 ± 2.7; p = 0.6) were comparable between the two groups. Moreover, in the infection group, there were 25 subjects (30.1% vs 9.6% in the control group, p < 0.001) with a regional peak systolic strain of the left ventricle below -16% in at least two segments. At multivariable logistic regression corrected for age, gender and body surface area, previous SARS-CoV-2 infection was an independent predictor of reduced LV-GLS values (p < 0.001). Conclusion: SARS-CoV-2 infection may affect left ventricular deformation in 30% of young adults patients despite an asymptomatic or only mildly symptomatic acute illness.  Speckle tracking echocardiography could help in early identification of patients with subclinical cardiac involvement. Since long-term complications of COVID-19 are not yet known, myocardial deformation imaging could be important for risk stratification, treatment and planning of long-term follow-up.